THE ROLE OF THE FUNCTION OF THE TALIABU ISLAND REGENCY DPRD IN THE PROCESS OF FORMING REGIONAL REGULATIONS - Helika Mansur; Jusan Hi Yusuf; Misrina Sergi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the role and function of the Regional Regulation Formation Agency (Bapemperda) of the Taliabu Island Regency DPRD in the process of forming regional regulations (Perda). The birth of Bapemperda as a fitting tool for the DPRD is a mandate of Law Number 12 of 2011 concerning the Formation of Laws and Regulations, which emphasizes the importance of the quality of regional legal products to be in harmony with the needs of the community and regional development. The research method used is a qualitative approach with data collection techniques through interviews, documentation, and literature studies. The results of the study show that the Bapemperda DPRD of Taliabu Island Regency plays an important role in the preparation of the Regional Regulation Formation Program (Propemperda), the discussion of the draft Regional Regulation, and providing legal considerations to the proposed regional regulations from the executive and legislative initiatives. However, in practice, the role of Bapemperda still faces various obstacles, such as limited human resources who understand legislative techniques, lack of public participation in the preparation of regional regulations, and suboptimal coordination between the DPRD and local governments. In conclusion, the Bapemperda of the Taliabu Island Regency DPRD has carried out the function of legislation according to its authority, but its effectiveness still needs to be improved through strengthening the capacity of members, increasing synergy between institutions, and encouraging community involvement in every stage of the formation of regional regulations so that the resulting regional regulations are truly aspirational, implementive, and effective for regional development